Identification of potent multi-target antiviral natural compounds from the fungal metabolites against aspartyl viral polymerases - Zohreh Sahhaf Razavi; Ali Ramazani; Armin Zarei (Scientific Reports)
Abstract Since viral polymerases are responsible for viral replication, they are a prime target in antiviral drug development. The present study evaluated the antiviral potential of 174 secondary metabolites of the Sordariales order against aspartyl polymerases, including hepatitis C virus nonstructural protein 5B (HCV NS5B) and Severe acute respiratory syndrome coronavirus 2 RNA-dependent RNA polymerase (SARS CoV-2 RdRp). A two-step virtual screening was performed, identifying 76 ligands binding to the active site, while 10 showed binding energies below -7 kcal/mol. Ligands 1–3 exhibited better binding affinities than the Ribavirin. Lig-3 demonstrated the most intense interaction. These interacted through hydrogen bonding and hydrophobic interactions with the key catalytic motifs that may disrupt viral replication by inhibiting polymerase activities. Next, the effects of these ligands induced in polymerase structure and dynamics were analyzed by 300 ns molecular dynamics (MD) simulations, showing that ligand binding altered structural dynamics in critical motifs responsible for NTP and RNA template binding. RMSF and PCA analyses revealed reduced protein mobility and significant structural destabilization, particularly for Lig-1 and Lig-3 in SARS-CoV-2 RdRp and Lig-2 and Lig-3 in HCV NS5B. Additionally, Rg and SASA analyses indicated structural compression in ligand-bound complexes, corroborating the hypothesis of enzymatic inhibition. MM/PBSA analysis highlighted Lig-1 and Lig-3 as having stronger binding energies for SARS-CoV-2 RdRp, while Lig-3 and Lig-2 displayed higher binding energies for HCV NS5B. With promising ADME/T properties, Lig-3 is a promising multi-target antiviral candidate against HCV NS5B and SARS-CoV-2 RdRp, meriting further in vitro and in vivo investigations.